2018
DOI: 10.1186/s12906-018-2230-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and in situ efficacy of Bidens pilosa Linn and Dichrostachys cinerea Wight et Arn extracts against common diarrhoea-causing waterborne bacteria

Abstract: BackgroundBidens pilosa and Dichrostachys cinerea extracts were investigated for the antibacterial properties against waterborne diarrhoeagenic bacteria.MethodsThe plant materials were extracted using the direct and serial exhaustive methods using solvents of varying polarities, namely, hexane, dichloromethane, ethyl acetate, acetone and methanol. Qualitative phytochemical analysis and quantitative determination of total phenolic content of the leaf powders of the two plants were tested. The antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…It has been reported previously that the water extract of different plants usually yields significantly higher amounts compared to ethanolic extracts of same plants ( Caleja et al, 2016 ). This may be due to using a high temperature for 30 min during extraction and also to the higher polarity of water ( Dhanani et al, 2017 ). In addition, the utilization of vibrations to rupture plant cell walls, resulted in releasing of compounds and molecules into the solvent ( Tiwari, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported previously that the water extract of different plants usually yields significantly higher amounts compared to ethanolic extracts of same plants ( Caleja et al, 2016 ). This may be due to using a high temperature for 30 min during extraction and also to the higher polarity of water ( Dhanani et al, 2017 ). In addition, the utilization of vibrations to rupture plant cell walls, resulted in releasing of compounds and molecules into the solvent ( Tiwari, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Afterward, the two beakers were transferred to incubator shaker and kept for overnight at 37°C and 150 rpm. The supernatant was similarly processed as described in conventional extraction to get dried extracts of selected plants as described by ( Dhanani et al, 2017 ). Dried extracts were dissolved in 10% DMSO for ethanolic extracts or in distal water for water extracts ( Gurnani et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dichrostachys cinerea is a shrub native to Africa. Its twigs are used in traditional treatments for acne vulgaris, while leaves and fruits are used for the treatment of diarrhea, fever and headache ( Shandukani et al, 2018 ). Twigs of D. cinerea extracted with dichloromethane and methanol (1:1) had an MIC against Staphylococcus epidermidis of 0.19 μg/mL ( Nciki et al, 2016 ); however, in the same study, no activity was found on eight other bacterial pathogens tested.…”
Section: Discussionmentioning
confidence: 99%
“…The phytochemical screening realized on Dichrostachys cinerea leaves has showed the presence of polyphenols, flavonoids and tannins [14][15][16][17][18][19][20][21][22][23][24][25][26] . These results are in line of others studies which already shown the presence of polyphenols, flavonoids and tannins in extract of leaves of Dichrostachys cinerea 27 .…”
Section: Discussionmentioning
confidence: 99%